2010
DOI: 10.1007/s00122-010-1383-9
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation of the β-, γ- and δ-kafirin genes in diverse Sorghum genotypes

Abstract: The β-, γ- and δ-kafirin genes were sequenced from 35 Sorghum genotypes to investigate the allelic diversity of seed storage proteins. A range of grain sorghums, including inbred parents from internationally diverse breeding programs and landraces, and three wild Sorghum relatives were selected to encompass an extensive array of improved and unimproved germplasm in the Eusorghum. A single locus exists for each of the expressed kafirin-encoding genes, unlike the multigenic α-kafirins. Significant diversity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Plant leaf samples were collected fresh or stored dried and extracted with a CTAB buffer method as described by Laidlaw et al 28 . PCR for genotyping was carried out with Bioline MyTaq HS (www.bioline.com.au) per the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Plant leaf samples were collected fresh or stored dried and extracted with a CTAB buffer method as described by Laidlaw et al 28 . PCR for genotyping was carried out with Bioline MyTaq HS (www.bioline.com.au) per the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…1D separation of the prolamin fraction revealed altered expression of β-kafirin in a 19kD protein band, present in 296B and absent in QL12 (Fig. 3.4, highlighted in white), as predicted based on previous molecular characterisation (167). On 2D gels differential expression of β-kafirin was identified in 296B…”
Section: Characterisation Of Kafirin Subclasses and The β-Kafirin Nulsupporting
confidence: 73%
“…Twenty eight inbred sorghum lines, with previously determined allelic variation in the β-, γ-, and δ-kafirin storage proteins were included in the study (167). The primary focus of the analysis was on comparisons between the β-kafirin null line QL12 and in 296B, an important food line of Indian origin.…”
Section: Plant Materialsmentioning
confidence: 99%
“…These markers were mainly used for genetic diversity, cultivar identification, gene mapping and discovery, and gene pyramiding. For instance, The β-, γ-and δ-kafirin genes were sequenced from 35 sorghum genotypes to investigate the allelic diversity of seed storage proteins (Laidlaw et al, 2010). Marker-assisted selection (MAS) is becoming an increasingly useful tool to breeders, and it is our goal to add them to the toolbox by providing a genetic analysis of sorghum protein digestibility.…”
Section: Characterisation Using Molecular Markers As New Technologiesmentioning
confidence: 99%
“…The γ-kafirin contains 9-12% of the total kafirin fraction and 19-21% of opaque endosperm, whereas the σ-kafirin contains 1% total seed storage protein. Laidlaw et al (2010) reported characterization of alleles for presence of genetic diversity among the seed storage proteins in sorghum cultivars. The sorghum cultivars were sequenced and characterised for grain protein quality where the β-kafirin showed large variation in grain quality, and cysteine rich γ-kafirin and σ-kafirin comprised less variation.…”
Section: Characterization Of Nutritional Quality: Protein and Amino Amentioning
confidence: 99%